Simultaneous integrated boost-intensity modulated radiation therapy (SIBIMRT) planning for pelvic tumours: dose coverage to target volume and normal tissue sparing - Marwa Ali Hussein,; Siham Sabah Abdullah,; Hadeel Kamil Abdullah,; Abdulrahman Mohammed Abdulbaqi,; Sura Abdul Kareem Madlool, (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the better radiotherapy plan for pelvic tumours that may achieve a high target coverage dose and low normal tissue tolerance dose using simultaneous integrated boost-intensity-modulated radiation therapy technique. Method: The analytical, cross-sectional, descriptive study was conducted from October 2020 to March 2021 at Al-Amal National Hospital for Cancer Treatment, Baghdad, Iraq, and comprised male pelvic cancer patients aged 50-80 years. Computed tomography scans were randomly selected. For each patient, 4 treatment plans (phases I and II) were generated using the simultaneous integrated boost-intensity-modulated radiation therapy technique while keeping all parameters constant except the number of beams, which were 5, 7, 9 and 11. The optimal and safe dose was defined as the one to cover 95% planning target volume. Homogeneity and conformity indices were used to assess the uniformity of dose distribution in the target volume, and various treatment plans in the same patient were compared. Data was analysed using SPSS 24. Results: There were 15 males with mean age 67.12±2.84 years. There was a significant variance in the target volume dose and organ at risk in the 4 different plans generated using the simultaneous integrated boost-intensitymodulated radiation therapy technique (p<0.05). The 9-beam treatment plan was the best for coverage of tumours and protection of healthy organs assessed through homogeneity and conformity indices (p<0.05). Conclusion: The 9-beam treatment plan showed significant tumour coverage, homogeneity and conformity values, and sparing dose for organs at risk. Key Words: Pelvic, Tomography, Radiotherapy, Radiation